Gp78 E3 Ubiquitin Ligase: Essential Functions and Contributions in Proteostasis - Joshi, Vibhuti; Upadhyay, Arun; Kumar, Amit; Mishra, Amit (Frontiers in Cellular Neuroscience, 2017)
As per the requirement of metabolism and fitness, normal cellular functions are controlled by several proteins, and their interactive molecular and signaling events at multiple levels. Protein quality control (PQC) mechanisms ensure the correct folding and proper utilization of these proteins to avoid their misfolding and aggregation. To maintain the optimum environment of complex proteome PQC system employs various E3 ubiquitin ligases for the selective degradation of aberrant proteins. Glycoprotein 78 (Gp78) is an E3 ubiquitin ligase that prevents multifactorial deleterious accumulation of different misfolded proteins via endoplasmic reticulum-associated degradation. However, the precise role of Gp78 under stress conditions to avoid bulk misfolded aggregation is unclear, which can act as a crucial resource to establish the dynamic nature of the proteome. Present article systematically explains the detailed molecular characterization of Gp78 and also addresses its various cellular physiological functions, which could be crucial to achieving protein homeostasis. Here, we comprehensively represent the current findings of Gp78, which shows its protein quality control roles in different physiological functions and diseases; and thereby propose novel opportunities to better understand the unsolved questions for therapeutic interventions linked with different protein misfolding disorders.